(untitled) (Journal of Coating Science and Technology, 2014)
Nanocrystalline silicon (nc-Si:H) thin films were deposited by capacitive coupled radio-frequency plasma enhanced chemical vapor deposition (RF-PECVD) system with direct current (DC) bias applied. Raman, XRD and ultraviolet-visible transmission spectra were employed to investigate their microstructure and optical properties, respectively. Both the crystalline volume fraction and the average crystalline size increase with the substrate temperature. With the increase of silane concentration, the crystalline volume fraction increases, while the average crystalline size decreases. With the increase of the radio frequency (RF) power or the DC negative bias voltage, the crystalline volume fraction and the average crystalline size increase firstly, then decreases. Finally, the optical band gaps were discussed in detail.